Dampak Pengangguran dan Penyaluran Dana Zakat Infak Sedekah terhadap Kemiskinan di Provinsi Kalimantan Selatan - Muhammad Ramadhani; Difi Dahliana (Ecoplan, 2022)
This study aims to determine the effect of unemployment and ZIS funds' distribution on South Kalimantan poverty. This is a quantitative study with secondary data in the form of time series data for 2012-2021 obtained from the Central Statistics Agency (BPS) and the National Amil Zakat Agency (BAZNAS). Based on the results of statistical analysis using the Eviews 9 application, it is assumed that all the requirements in the classical assumptions are met so that multiple linear regression analysis can be carried out with t-test and f-test. The results of this study indicate that the unemployment rate and the distribution of ZIS funds simultaneously have a significant effect on the poverty level in South Kalimantan. However, partially, only the unemployment rate has a considerable effect. In contrast, the distribution of ZIS funds does not have a substantial impact because consumptive, not productive; programs still dominate the distribution pattern of ZIS funds. Therefore, this study resulted in a recommendation to increase the distribution of ZIS funds productively to impact poverty alleviation in South Kalimantan significantly.